The Impact of Transformational Leadership Style And Work-Life Balance on Enhancing Employee Engagement of Generation-Z Employees at PT PNM Mekaar Business Unit Regional Aceh With Social Support as an Intervening Variable - Utomo, Agung; M.C Oetami Prasadjaningsih (International Journal of Education, Vocational and Social Science, 2025)
This study employs a quantitative research approach, which relies on the collection of numerical data derived from measurements. As such, statistical analysis plays a vital role in addressing the research questions. The population in this study comprises all Generation Z employees of PT. PNM Mekaar Business Unit in the Aceh Region, totaling 856 individuals. The sampling technique used is stratified random sampling, where individuals are randomly selected from each stratum to form the sample. The results of this study are as follows: (1) Transformational Leadership Style has a positive effect on Social Support; (2) Work Life Balance has a positive effect on Social Support; (3) Transformational Leadership Style has a positive effect on Employee Engagement; (4) Work Life Balance has a positive effect on Employee Engagement; (5) Social Support has a positive effect on Employee Engagement; (6) Social Support significantly mediates the relationship between Work Life Balance and Employee Engagement; (7) Social Support significantly mediates the relationship between Transformational Leadership Style and Employee Engagement; (8) Transformational Leadership Style and Work Life Balance collectively influence Social Support by 51.1%; and Transformational Leadership Style, Work Life Balance, and Social Support collectively influence Employee Engagement by 86.7%.